Indian Buddhist philosophy - Carpenter, Amber D.; Cambridge eBooks (Durham : Acumen Publishing, 2014)
Organised in broadly chronological terms, this book presents the philosophical arguments of the great Indian Buddhist philosophers of the fifth century BCE to the eighth century CE. Each chapter examines their core ethical, metaphysical and epistemological views as well as the distinctive area of Buddhist ethics that we call today moral psychology. Throughout, the book follows three key themes that both tie the tradition together and are the focus for most critical dialogue: the idea of an?tman or no-self, the appearance/reality distinction and the moral aim, or ideal. Indian Buddhist philosophy is shown to be a remarkably rich tradition that deserves much wider engagement from European philosophy. Carpenter shows that while we should recognise the differences and distances between Indian and European philosophy, its driving questions and key conceptions, we must resist the temptation to find in Indian Buddhist philosophy, some Other, something foreign, self-contained and quite detached from anything familiar. Indian Buddhism is shown to be a way of looking at the world that shares many of the features of European philosophy and considers themes central to philosophy understood in the European tradition.
The Buddha's suffering -- Practice and theory of no-self -- Klesas and compassion -- The second Buddha's greater vehicle -- Karmic questions -- Irresponsible selves, responsible non-selves -- The third turning: Yogacara -- The long sixth to seventh century: epistemology as ethics.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Buddhist philosophy -- History; Religious thought -- To 600.; Electronic books